Immunogenicity and safety of ebolavirus vaccines in healthy adults: a systematic review and meta-analysis of randomized controlled trials - Juntao Yin; Liang Zhang; Chaoyang Wang; Changjiang Qin; Mingsan Miao (Taylor & Francis Group, 2024)
ABSTRACTBackground This review aimed to systematically evaluate the immunogenicity and safety of the candidate Ebola virus vaccine (EVV).Methods We searched five databases for randomized controlled trials (RCTs) evaluating the effects of EVV on healthy adults. The primary outcomes were relative risk (RR) of sero-conversion or sero-response of EVV in healthy adults between the groups that received EVV and the controls.Results Twenty-nine RCTs (n = 23573) were included. There was a significant difference in RR of sero-conversion of EVV (RR 13.18; 95% CI 11.28-15.41; I2 = 33%; P < 0.01) between the two groups. There was a significant difference in RR of adverse events (AEs) of EVV (RR 1.49; 95% CI 1.27-1.74; I2 = 88%; P < 0.01), although no difference in RR of serious AE (SAE) between the two groups. Subgroup analysis showed that there was no significant difference in RR of AEs for DNAEBO, EBOV-GP, MVA, and rVSVN4CT1 vaccines, compared with controls.Conclusions The DNAEBO, EBOV-GP, MVA, and rVSVN4CT1 vaccines are likely to be safe and immunogenic, tending to support the vaccination against Ebola disease. These findings should provide much-needed evidence for public health policy makers to develop preventive measures based on disease prevalence features and socio-economic conditions.